Optical coherent tomographic angiographic pattern of the deep choroidal layer and choriocapillaris after photodynamic therapy for central serous chorioretinopathy - Chan, Szy Y.; Pan, Chung Ting; Wang, Qian; Shi, Xue Hui; Jonas, Jost B.; Wei, Wen Bin (Graefe's archive for clinical and experimental ophthalmology, 2019)
PurposeTo study the changes in the choroidal vascular pattern of the deep choroidal layer and choriocapillaris in the eyes with central serous chorioretinopathy (CSC) before versus after photodynamic therapy (PDT) as visualized by optical coherence tomography angiography (OCTA).MethodsThis comparative case series study included patients who underwent a half-dose of PDT as a therapy for CSC. Using OCTA and manually shifting the reference level into the deep choroidal layer, we assessed the density of the deep choroidal vascular layer and choriocapillaris.ResultsThe study included 20 patients (17 men; mean age, 43.3 ± 10.9 years), with two patients showing bilateral CSC. In the eyes affected by CSC, the mean vascular density of the deep choroidal layer and choriocapillaris increased significantly from 54.2 ± 6.7% at baseline to 58.0 ± 4.7% at 1 month after PDT (P = 0.002) and from 58.1 ± 2.7% at baseline to 60.5 ± 2.7% at 1 month after PDT (P = 0.004), respectively. The difference between affected and unaffected eyes was significantly larger at baseline than at 1 month after PDT (deep choroidal layer 4.79 ± 6.02 versus 0.39 ± 3.46, P = 0.002; choriocapillaris 4.26 ± 3.94 versus 1.25 ± 3.44, P = 0.002) and larger than at 3 months after baseline (n = 11 patients), when the affected and unaffected fellow eyes no longer differed significantly (P = 0.66 and P = 0.37, respectively). As a corollary, the width of the large choroidal vessels in the deep choroidal layer decreased after the PDT. Comparing assessments by two blinded examiners revealed a kappa value of 0.90, indicating a good agreement for examination of the deep choroidal layer.ConclusionIn conclusion, OCTA can be helpful to visualize the deep choroidal vascular layer by manually shifting the reference layer deeper into the choroid.